AB0483 Responsiveness of lupus impact tracker among chinese patients with lupus. (15th June 2017) - Mok, CC; Block, J; Jolly, M
Abstract : Background: Lupus Impact Tracker (LIT), a 10 item, patient reported outcome tool for patients with systemic lupus erythematosus (SLE) has undergone psychometric validation and responsiveness studies in the US and Europe. Objectives: To report results on responsiveness of Lupus Impact Tracker among Chinese patients with SLE. Methods: 430 patients with SLE meeting the ACR classification criteria were recruited in Hong Kong, China at a single center. LIT scores from two visits one year apart were analyzed for responsiveness and Minimal Clinically Important Difference (MCID) against patient report and physician assessed anchors of changes in health. Two patient reported anchors were used (Global change in health and item 2 of Short Form 36 form). Physician assessed anchors of change in health were disease activity (Physician global assessment-PGA, SELENA-SLEDAI) and damage (SLICC-SDI/ACR). Change in PGA of ≥0.3 and SELENA-SLEDAI of ≥4 in either direction was used to define worsening in disease activity. Analysis of variance was used to compare changes in LIT score against the anchors. Results: Mean (SD) age of participants was 42 (14) years. Ninety five percent were women. Mean (SD) PGA, SELENA-SLEDAI and SDI at baseline were 0.5 (0.5), 2.9 (3.0) and 0.7 (1.2) respectively. Mean (SD) LIT score at baseline was 27.8 (18.2). Mean changes in LIT scores in response to worsening, no change or improvement based on patient report and physician assessments are shown in Table 1 . MCID for "some worsening" were -4.0 and -3.9 on patient reported health question and SF36 question 2 respectively. Conclusions: LIT shows responsiveness to changes in both patient-reported and physician assessed changes in health status among Chinese SLE patients. Disclosure of Interest: None declared